Oncological adequacy of R1 vascular margin in minimally invasive liver surgery for hepatocellular carcinoma and colorectal liver metastases: a meta-analysis - Procopio, Fabio; Memeo, Riccardo; Del Fabbro, Daniele; Abdelhadi, Schaima; Reißfelder, Christoph; Edwin, Bjørn; Milana, Flavio; Troisi, Roberto Ivan; Torzilli, Guido; Caringi, Silvio; Valle, Raffaele Dalla; Giuffrida, Mario; et al. (Annals of surgical oncology, 2026)
The concept of tumor-vessel detachment (R1 vascular [R1v]), has recently gained attention within the minimally invasive (MI) setting, but its oncological adequacy remains poorly defined. This meta-analysis aims to assess the outcomes of MI-R1v hepatectomy for hepatocellular carcinoma (HCC) and colorectal liver metastases (CLM).